Nickel‐Catalyzed Cycloaddition of 1, 3‐Dienes with 3‐Azetidinones and 3‐Oxetanones1. Issue 46 (23rd September 2013) - Thakur, Ashish; Facer, Megan E.; Louie, Janis
<x xml:space="preserve">Abstract</x> A growth and expansion strategy: A Ni/P(p‐tol)3‐catalyzed cycloaddition of 1, 3‐dienes with 3‐azetidinones and 3‐oxetanones produced eight‐membered heterocycles with a variety of substituents (see scheme; Boc=tert‐butoxycarbonyl). The synthesis of the reduced azocine and oxocine derivatives involved the challenging steps of C(sp2)C(sp3) bond activation and C(sp3)C(sp3) reductive elimination.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>